1999
DOI: 10.1143/jjap.38.l1134
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Films Prepared by Liquid Source Chemical Vapor Deposition Using Bis-(ethylcyclopentadienyl)ruthenium

Abstract: Ruthenium (Ru) films were deposited by liquid source chemical vapor deposition using bis-(ethylcyclopentadienyl)ruthenium (Ru(C2H5C5H4)2). The crystalline structure, resistivity and residual impurities in the Ru films were investigated. The Ru films were polycrystalline and had a columnar structure; they showed a low resistivity of about 20 µΩ cm, which is sufficiently low for them to be used as capacitor electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…However, these precursors are not ideal for CVD due to their high melting points. Because of the difficulties with solid precursors, liquid precursors such as Ru(EtCp) 2 [21,22] and Ru(OD) 3 [23] (OD = 2,4-octanedionate)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these precursors are not ideal for CVD due to their high melting points. Because of the difficulties with solid precursors, liquid precursors such as Ru(EtCp) 2 [21,22] and Ru(OD) 3 [23] (OD = 2,4-octanedionate)…”
Section: Introductionmentioning
confidence: 99%
“…The deposited ruthenium metal itself is not oxidized during the process. Oxygen-containing gas mixtures are commonly used oxidants in respective CVD processes, [2,19,21,22] and thus they might also work in ALD even though, in ALD oxide studies, oxygen has been found to be too inert to react with most of the metal precursors. [26] For the ruthenium precursor, sufficient thermal stability and high reactivity with oxygen are the most critical requisites.…”
Section: Introductionmentioning
confidence: 99%
“…Several ruthenium compounds have been investigated as MOCVD precursors to produce pure ruthenium films. However, limitations reduce the applicability of these substances; Ru(C 5 H 5 ) 2 [2,3] and Ru(acac) 3 [1,4] decompose at such high temperatures that they are incompatible with integrated circuits, whilst the carbonyl complexes Ru(CO) 5 and Ru 3 (CO) 12 [1,5] are toxic, and RuO 4 may be explosive when heated to 100 C and above. [6] Another problem is a significant carbon contamination of the thin films when Ru(C 5 H 4 Et) 2 , [3] [(Ru(C 5 H 5 )(CO) 2 ] 2 , [7] Ru(tmhd) 3 (tmhd = 2,2,6,6-tetramethylheptane-3,5-dione), [8±10] Ru(CO) 2 (tmhd) 2 , [11] and Ru(1,5-COD)(g 3 -allyl) 2 (1,5-COD = 1,5-cyclooctadiene) [12] are used.…”
Section: Introductionmentioning
confidence: 99%
“…Ru is used as an electrode for these dielectric materials due to its dry etchability and high conductivity under oxidizing conditions. [5,6] Recently, a Ta 2 O 5 film grown on a Ru(002) film and annealed at 800 C [7] was found to have a dielectric constant at its highest level of 110, due to the delocalized electrons in the hexagonal crystal structure. [8] Considering process maturity, feasibility, and reliability, [9] Ru±Ta 2 O 5 ±Ru is regarded as an attractive structure for a metal±insulator±metal (MIM) capacitor.…”
Section: Introductionmentioning
confidence: 99%
“…Although a Ru thin film grown by physical vapor deposition (PVD) has good material characteristics, [7] it has to be grown by CVD to meet the step coverage required for the bottom electrode of a DRAM capacitor. [6] Studies of Ru MOCVD began only in the last few years, and its deposition mechanism has not yet been clearly established.…”
Section: Introductionmentioning
confidence: 99%